UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR AKIDAH AKHLAK MELALUI MULTIMEDIA LCD PROYEKTOR - Dedi Wahyudi; Devi Septya Wardani (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2017)
This study aims to determine the increased activity and learning outcomes akidah morals through multimedia LCD Projector. The method used in this research is library research. Data collection is obtained through documentation studies of related scientific works. The type of research is qualitative ie that produces analytical procedures that do not use statistical analysis procedures or other qualifications. Based on the results of the study concluded that the application of media: (1) Increase student learning activities. This is based on literature studies that researchers get. (2) Improve learning outcomes. This is based on literature studies that researchers obtain, from the results of pre-cycle learning has increased.